Dynamic Management of Lung Cancer Care During Surging COVID-19 - Wang, Annie; Chang, Stephanie H.; Kim, Eric J.; Bessich, Jamie L.; Sabari, Joshua K.; Cooper, Benjamin; Geraci, Travis C.; Cerfolio, Robert J. (Frontiers in Surgery, 2021)
Management of patients with lung cancer continues to be challenging during the COVID-19 pandemic, due to the increased risk of complications in this subset of patients. During the COVID-19 surge in New York City, New York University Langone Health adopted triage strategies to help with care for lung cancer patients, with good surgical outcomes and no transmission of COVID-19 to patients or healthcare workers. Here, we will review current recommendations regarding screening and management of lung cancer patients during both a non-surge phase and surge phase of COVID-19.